Sulfate Mobility in Fen Peat and Its Impact on the Release of Solutes - Gosch, Lennart; Townsend, Heather; Kreuzburg, Matthias; Janssen, Manon; Rezanezhad, Fereidoun; Lennartz, Bernd (Frontiers in Environmental Science, 2019)
Sea-level rise coupled with land subsidence from wetland drainage exposes increasingly large areas of coastal peatlands to seawater intrusion. Seawater contains high concentrations of sulfate (SO42-), which can alter the decomposition of organic matter thereby releasing organic and inorganic solutes from peat. In this study, a flow-through reactor system was used in order to examine the transport of SO42- through peat as well as its effect on solute release. Moderately-decomposed fen peat samples received input solutions with SO42- concentrations of 0, 100, 700 and 2700 mg L-1; sample effluent was analyzed for a variety of geochemical parameters including dissolved organic carbon (DOC), dissolved inorganic carbon (DIC) and total dissolved nitrogen (TDN) as well as the concentrations of major cations and anions. The input solution remained anoxic throughout the experiment; however, no signs of a pronounced SO42- reduction were detected in the effluent. SO42- transport in the fen peat resembled non-reactive bromide (Br-) transport, indicating that in the absence of SO42- reduction the anion may be considered a conservative tracer. However, slightly elevated concentrations of DOC and TDN, associated with raised SO42- levels, suggest the minor desorption of organic acids through anion exchange. An increased solute release due to stimulated decomposition processes, including SO42- reduction, was observed for samples with acetate as an additional marine carbon source included in their input solution. The solute release of peats with different degrees of decomposition differed greatly under SO42--enriched conditions where strongly-decomposed fen peat samples released the highest concentrations of DOC, DIC and TDN. Overall, besides a cation-exchange related release of substances adsorbed in the peat, an input of increased SO42- concentrations in a peatland by itself might not lead to an increased solute release in the short-term. However, once SO42- reduction has commenced following long-term anoxic conditions or due to a biologically readily degradable carbon source, a SO42- input can stimulate the release of solutes, including DOC, DIC and TDN, from peat.